PERGOLAKAN PRRI DI KECAMATAN XIII KOTO KAMPAR TAHUN 1958-1961 - Muzaki, Muhammad Fikri; Melay, Hum, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : PRRI are part of the history of the Indonesian Nation. The story of PRRI i.e. regional efforts reminded the Government at first because of their lack of attention to the region. According to people, the PRRI also had a large role in the attempt of independence as well as various attempt after that to maintain the independence of the Republic of Indonesia. An unsuccesful attempt was later continued with psyical contact i.e. civil war. The outbreak of the war of the ultimatum to Central Government not was granted. During the war that is synonymous with the region of West Sumatera, but also occurs in district XIII Koto Kampar, Kampar Regency, Riau Province. This research aims (1) to know the history of the founding of PRRI (2) to find out the factors that led to the inception of PRRI (3) to find out the background of occurence of upheaval PRRI in district XIII Koto Kampar 1958-1961 (4) to find out what kind of shape the throes of PRRI in district XIII Koto Kampar (5) to find out the who the character involved in the throes of PRRI in district XIII Koto Kampar (6) to find out how the condition of the community sub-district XIII Koto Kampar after PRRI churned. The methods used ini this research is qualitative and historical methods. Data obtained from the results of the interviews and then analyzed with language of its own. As for the location of the research that is in district XIII Koto Kampar, Kampar Regency, Riau Province. In research time starts from the collection of data, then the proposal colloquim as well as up to the scription examination. Data collection techniques are used interview techniques, documentations techniques, and literature study techniques.Keyword: PRRI Upheaval, in District XIII Koto Kampar